PERAN ORANG TUA DALAM MENINGKATKAN KETAATAN ANAK TERHADAP ALLAH MELALUI DISIPLIN SHALAT FARDHU DI KELURAHAN KURAO PAGANG - Erawati; Zulfamanna; Rizal Safarudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of parents in enhancing children’s obedience to Allah through discipline in performing obligatory prayers (shalat fardhu) in Kurao Pagang Village. The research employed a qualitative field research approach with a descriptive design to explore religious practices within the family environment. The research subjects were parents with elementary school–aged children. Data were collected through interviews, observations, and documentation. Data analysis was conducted inductively through data reduction, data display, and conclusion drawing, while data validity was ensured using source and technique triangulation.The findings indicate that parents play a significant role in fostering children’s obedience in performing obligatory prayers. Open and persuasive communication, accompanied by consistent parental role modeling, serves as a key factor in shaping children’s religious awareness. Parents apply various educational methods, including exemplary behavior (uswah hasanah), habituation, positive reinforcement, emotional approaches, and disciplined supervision adjusted to the child’s age and character. However, several challenges were identified, such as children’s laziness, low spiritual awareness, negative influences of digital media, limited parental time, and unsupportive peer environments. Despite these obstacles, parents continue to demonstrate adaptive efforts and collaborate with social and religious figures to overcome these challenges. The study concludes that effective parental involvement within the family is essential in developing children’s discipline and consistency in performing obligatory prayers.